Image Steganography Based on Edge Detection and the Average Values between Edge Points (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Steganography aims to hide a message or generally a file in some cover medium with hiding the existence of the secret message. Many medium can be used as carriers or covers, but images still the most popular due to its heavy use in the internet and its higher amount of data that can be used to hide more secret data. In this paper, a new approach for concealing secret text message within color image is introduced. It depends mainly on using the three red, green and blue bands of the color cover image as three independent grayscale images, then using different edge detector for each one. After finding these edges, the secret text message bits are divided into three segments, each concealed within different grayscale image by utilizing the strongest edges first. The embedding of the secret message bits is implemented by calculating the average value between each two adjacent edge pixels for concealing one bit.